Study Habits and Learning Performance Of Grade 6 Indigenous Learners In A District - Fredeluces, Rolando B. (Future Science / FSH-PH Publications, 2024)
Indigenous students faced various challenges that could hinder their academic success. The Indigenous Peoples' Rights Act (IPRA), the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP), and the Indigenous Peoples' Education (IPEd) Policy and Framework (DepEd Order No. 32, s. 2015) all contributed to strengthening the indigenous rights movement. The research sought the influence of study habits on the academic achievement of Grade 6 indigenous students in the District of San Marcelino. The goal was to improve the quality of education through effective classroom instruction. The research investigated the correlation between study habits and academic achievement in Grade 6 IPEd students in the 2022-2023 school year. Two factors were considered: individual factors such as age, gender, birth order, mother's highest educational attainment, and father's highest educational attainment, as well as instructional factors such as interest and study habits. The research was done in San Marcelino District Schools, Division of Zambales. The participants were randomly selected from eight out of the twenty-one public elementary schools in the district. The main instrument of the data was a survey questionnaire. The collected data were analyzed using simple statistical tools, including frequency count, mean, standard deviation, and inferential statistics. The hypothesis was tested using F-Test or ANOVA and Pearson R Correlation at a significance level of 0.05. The findings indicated that the participants had a diverse mix in age, gender, birth order, and their parents' education. Most participants were between 11 and 12 years old, with an almost equal number of males and females. The distribution of birth order varied, with a majority being either the first-born or fifth-born or above. Furthermore, the parents' educational background ranged from elementary education to college. The study found a correlation between the academic performance of Grade 6 IPED learners and their study habits. This correlation was moderate in strength and statistically significant, indicating that IPED learners with good study habits had a higher likelihood of achieving higher grades.